Crude glycerin in steam-flaked corn-based diets for beef cattle - Parsons, G.L.; Shelor, M.K.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Plant oils contain large amounts of triglycerides that will react to a catalyst, such as methanol. The transesterification reaction between the oil and alcohol will produce approximately 10% crude glycerin and 90% biodiesel. Crude glycerin is distilled for use in human products such as soaps, cosmetics, and moisturizers, but the usefulness of glycerin as a feed source for livestock is unclear. Rapid expansion of the biodiesel industry has created excess supplies of crude glycerin. It is thought that glycerin can be used in ruminant diets to decrease feed costs, but crude glycerin from biodiesel production can contain various levels of methanol, which can be toxic to livestock at increased levels. The purpose of this experiment was to determine the effects of feeding crude glycerin derived from soybean oil in steam-flaked corn finishing diets fed to beef cattle.
Keywords: Beef; Cattle; Crude glycerin; Soybean oil